Perspektif Masyarakat Palembang Terhadap Situs Bukit Seguntang Sebagai Pusat Agama Buddha - Andhifani, Wahyu Rizky; Kurniawati; Darme, Made; Susanti, L.R. Retno; Hudaidah, Hudaidah; Wahyudi, Wanny Rahadjo (Badan Riset dan Inovasi Nasional (BRIN), 2024)
This research aims to describe and analyze the perspectives of the people of Palembang on the Bukit Seguntang Site as the center of Buddhism. The method used qualitative description with the use of statistics to compile and display data as material for verification and interpretation. The results of this research showed that the people of Palembang did not know Seguntang Hill as a sacred place for Buddhist adherents, and its existence is only known as a sacred public cemetery. In addition, the people of Palembang have very little knowledge about the impact of development on historic sites even though it is stated in the Cultural Heritage Regulations of the Law of the Republic of Indonesia Number 11 in 2010. Even though it has been stated in government regulations, the construction of galleries, cafes, and parks is still being built without taking into account the identity of the historical values ​​of Seguntang Hill.